A Mine Is a Terrible Thing to Waste: High Content, Single Cell Technologies for Comprehensive Immune Analysis. Issue 5 (23rd February 2015) - Chattopadhyay, P. K.; Roederer, M.
Abstract : In recent years, an incredible variety of single cell technologies have become available to analyze immune responses. These technologies include polychromatic flow cytometry, mass cytometry, highly multiplexed single cell qPCR, RNA sequencing, microtools, and high‐resolution imaging. In this article, we review these platforms, describing their power and limitations for comprehensive analysis of the immune system. We relate the properties of these technologies to the various cellular states relevant to an immune response, in order to address which technologies are most appropriate for which settings. Abstract : This article reviews new single cell platforms for comprehensive analysis of immune responses.